1995
DOI: 10.1136/bjo.79.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, systemic blood pressure, smoking, and blood viscosity on orbital blood velocities.

Abstract: The influence of multiple systemic factors upon the blood velocities obtained from the orbital circulations was investigated. The velocities obtained by colour Doppler imaging from the ophthalmic artery, central retinal artery, and vein from 95 ophthalmologicaliy healthy volunteers were analysed. The effects of age, systemic blood pressure, and smoking habit were examined. In 24 volunteers blood viscosity was also measured and its relation with blood velocity assessed. Age was weakly negatively correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 20 publications
2
69
1
9
Order By: Relevance
“…Our data analysis should not have been biased by this factor since gender seems to make no difference in orbital blood-flow parameters (Williamson et al 1995). Intraocular pressure was significantly higher (pΩ 0.02) in early glaucoma (16.7∫3.1) than that in late glaucoma (13.6∫3.0) and in the control (14.3∫2.6).…”
Section: Resultsmentioning
confidence: 79%
“…Our data analysis should not have been biased by this factor since gender seems to make no difference in orbital blood-flow parameters (Williamson et al 1995). Intraocular pressure was significantly higher (pΩ 0.02) in early glaucoma (16.7∫3.1) than that in late glaucoma (13.6∫3.0) and in the control (14.3∫2.6).…”
Section: Resultsmentioning
confidence: 79%
“…Fume particles and noxious gases such as nicotine and carbon monoxide may influence the circulatory system by inducing profound vasospasm, platelet aggregation, or leading to oxidative damage to lipids, proteins, and cellular DNA. [2][3][4][5][6][7][8] Epidemiological data link cigarette smoking as a risk factor for many ophthalmological disorders including strabismus in offspring of pregnant smokers, anterior ischaemic optic neuropathy, age related macular degeneration, cataract, thyroid ophthalmopathy, primary open angle glaucoma, diabetic retinopathy, uveal melanoma, conjunctival intraepithelial neoplasia, ocular sarcoidosis, and development of dry eyes. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Beaver Dam Study related current active smoking and past history of smoking to a higher prevalence of dry eye disease.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study it has been observed that age is weakly negatively correlated with blood velocities in the ophthalmic artery. 19 Moreover, we studied subjects with mild untreated hypertension, because any form of anti-hypertensive medication may affect ocular blood flow. [20][21][22] Finally, we focused on subjects with SBPr160 mmHg and DBFr100 mmHg based on the evidence that even mild hypertension may induce an additional risk for progression of diabetic retinopathy in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%